2020
DOI: 10.1213/ane.0000000000004767
|View full text |Cite
|
Sign up to set email alerts
|

Role of Micro-RNA for Pain After Surgery: Narrative Review of Animal and Human Studies

Abstract: One of the most prevalent symptoms after major surgery is pain. When postoperative pain treatment is unsatisfactory, it can lead to poor surgical recovery, decreased quality of life, and increased health care costs. Current analgesics, single or in combination, have limited efficacy due to low potency, limited duration of action, toxicities, and risk of addiction. The lack of nonaddictive strong analgesics along with the over prescription of opioids has led to an opioid epidemic in the United States. Therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 140 publications
(162 reference statements)
0
5
0
Order By: Relevance
“…As a double-edged sword, SCs, critical peripheral nervous system components, are continually exposed to physiological and mechanical stressors during movement due to dynamic stretching and compression pressures [ 10 , 11 ]. SC-EVs transmit cargo to promote peripheral nerve regeneration in vitro [ 11 ], but they also play a role in nociceptive hypersensitivity [ 39 ]. Here, we discovered for the first time that, compared to those in sham rats, SC-EVs in the hippocampus were significantly enriched in CNP rats by generating three classic models of CNP, namely CCI, SNI, and SNI (14 days after modeling), overexpressing specific SC promoters using AAVs containing CD63-GFP.…”
Section: Discussionmentioning
confidence: 99%
“…As a double-edged sword, SCs, critical peripheral nervous system components, are continually exposed to physiological and mechanical stressors during movement due to dynamic stretching and compression pressures [ 10 , 11 ]. SC-EVs transmit cargo to promote peripheral nerve regeneration in vitro [ 11 ], but they also play a role in nociceptive hypersensitivity [ 39 ]. Here, we discovered for the first time that, compared to those in sham rats, SC-EVs in the hippocampus were significantly enriched in CNP rats by generating three classic models of CNP, namely CCI, SNI, and SNI (14 days after modeling), overexpressing specific SC promoters using AAVs containing CD63-GFP.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies have suggested that EXOs can modulate immune responses and promote the healing process, thereby potentially alleviating inflammation and pain [ 125 ]. Indeed, EXOs can suppress the production of proinflammatory cytokines such as TNF-α,IL-1β, and PGE2 in tissue-injured areas and also stimulate the release of IL-10, leading to antinociceptive effects [ 126 ]. Exosomal miRNAs like miR-181c-5p, miR-216a-5p, and miR-126-3p have also been demonstrated to ameliorate neuropathic pain in sciatic nerve compression in in vivo studies [ 123 , 127 ].…”
Section: Exosomes Ameliorate Neuropathic Painmentioning
confidence: 99%
“…It is also important to report the role that micro-RNAs (miRNAs) might play in opioid response and pain. In fact, it has been observed that commonly used analgesics altered their expression [63]. One example is miR-339-3p, the expression of which was consistently increased by both morphine and fentanyl.…”
Section: Animal Models' Studiesmentioning
confidence: 99%
“…Then, it was demonstrated that miR-339-3p destabilizes MOR mRNA and thus inhibits the MOR protein biosynthesis [25]. In nociception, the altered expression of many miRNAs was described in the context of surgical pain models, and some of them were related to morphine tolerance [63]. Chronic morphine treatment was observed to increase BDNF transcription and translation.…”
Section: Animal Models' Studiesmentioning
confidence: 99%